Studies of the hydration of tricalcium silicate - Le Sueur, P (1984)
The hydration reaction of tricalcium silicate and the various factors which influence it have been investigated using calorimetry, thermogravimetry, quantitative X-ray diffractometry, scanning and transmission electron microscopy and energy dispersive X-ray analysis. Various factors associated with the synthesis and subsequent storage of tricalcium silicate were found to alter its reactivity and it is thought that these may be responsible for much of the variability in the reported reactivity of tricalcium silicate preparations. The contribution of the individual factors (such as particle size distribution and impurity ion content) to such reactivity changes was investigated. Use of the Avrami equation to model the rate of heat output curves obtained by calorimetry was found to give good fits to the experimental data. Apparent activation energies of control and calcium chloride accelerated reactions were determined from the rate parameters derived from the fitting procedure. However, it is shown that the amount of mechanistic information which can be obtained from such a fitting procedure is limited. Observation of the detailed chemical and morphological changes occurring during the hydration of tricalcium silicate and the manner in which they are influenced by incorporation of calcium chloride (as a model accelerator) and sucrose (as a model retarder) show that during the later stages of hydration the chemistry of the reaction is not affected by the presence of the admixtures, but that their incorporation does cause some changes in the microstructure of the gel product.